2003
DOI: 10.1038/oby.2003.202
|View full text |Cite
|
Sign up to set email alerts
|

Prior Exercise Increases Dietary Oleate, but Not Palmitate Oxidation

Abstract: VOTRUBA, SUSANNE B., RICHARD L. ATKINSON, AND DALE A. SCHOELLER. Prior exercise increases dietary oleate, but not palmitate oxidation. Obes Res. 2003; 11:1509 -1518. Objective: Higher levels of physical activity have been associated with body weight maintenance, but previous work in our laboratory suggests that this is not purely related to energy balance. We hypothesize that this may be related to the partitioning of dietary fat between oxidation and storage. Research Methods and Procedures: Healthy women (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
5
24
2
Order By: Relevance
“…Of note, however, when all time-points of dose recovery were incorporated into the statistical analysis, there was a significant increase in dose recovery of dietary oleate and palmitate with exercise compared with sedentary conditions. That statistical difference was due to increases in dose recovery in the morning and evening postexercise periods, which is in agreement with previous reports (35). In the hours following the time when the exercise treatment was performed, dose recovery increased more for sedentary conditions, and the dose recovery "catches up" with that of the exercise conditions leading to the same 24-h dose recovery for both exercise and sedentary conditions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of note, however, when all time-points of dose recovery were incorporated into the statistical analysis, there was a significant increase in dose recovery of dietary oleate and palmitate with exercise compared with sedentary conditions. That statistical difference was due to increases in dose recovery in the morning and evening postexercise periods, which is in agreement with previous reports (35). In the hours following the time when the exercise treatment was performed, dose recovery increased more for sedentary conditions, and the dose recovery "catches up" with that of the exercise conditions leading to the same 24-h dose recovery for both exercise and sedentary conditions.…”
Section: Discussionsupporting
confidence: 81%
“…The ratio of unsaturated fats to saturated fats in the diet has been shown to influence energy substrate utilization in humans (14). Furthermore, acute exercise has been shown to increase dietary oleate oxidation but not palmitate oxidation (35). Therefore, the purpose of this study was to examine the effects of a high saturated (primarily palmitic acid) vs. high mono-unsaturated (primarily oleic acid) fat diet on how quickly the body can adapt to a HF diet by increasing fat oxidation (and decreasing NPRER) during both exercise and sedentary conditions.…”
mentioning
confidence: 99%
“…Enhanced fat oxidation from activity diminishes fat available for storage into body depots, 30,31 and especially VPA increases oxidation of certain fats. 32 Our data showed no relation of MPA with %BF; perhaps the amount of MPA was insufficient to affect %BF. Of the sedentary behaviours examined, only TV/MOVIE positively predicted part of the variance in %BF.…”
Section: Discussioncontrasting
confidence: 64%
“…Recently, Toth and Tchernof 4 have suggested that alterations in the partitioning of fat towards oxidation may play a significant role in the age-related increases in adiposity, and we have recently provided evidence that exercise, compared to rest, alters the partitioning of dietary fat towards oxidation rather than storage. 5,6 This ability to alter the partitioning of dietary fatty acids towards oxidation is possibly one of the beneficial effects of exercise, and may play a role in the protective effects of exercise against obesity and/or weight gain.…”
Section: Introductionmentioning
confidence: 99%